Combined hormonal contraception and its effects on mood: a critical review. (2nd September 2016) - Schaffir, Jonathan; Worly, Brett L.; Gur, Tamar L.
Abstract: Objectives: Adverse mood changes are sometimes cited as a reason for discontinuing combined hormonal contraception (CHC). A systematic review of recent literature was undertaken to characterise the nature of these side effects and identify characteristics that might predispose women to such effects. Methods: A MEDLINE review of studies from the past 30 years that focused on CHC and mood was performed. Database search was supplemented with studies found through citations and references. Results: The research literature on this topic is limited by a lack of prospective studies, a variety of measurements of mood, and a consolidation of many disparate types of contraceptives studied together in a single cohort. Common themes that emerge from review of these papers include (1) most women using CHC demonstrate no effect or a beneficial effect on mood, with a low incidence of adverse effects; (2) contraceptives containing less androgenic progestins may have fewer adverse effects on mood; (3) continuous and perhaps non-oral dosing of CHC has the fewest mood effects; (4) women with underlying mood disorders may be predisposed to mood effects, but this may reflect factors related to choice of contraception rather than the mood disorder itself. Conclusion: Inconsistent research methods and lack of uniform assessments make it difficult to make strong conclusions about which CHC users are at risk for adverse mood effects. Until more prospective data is available, clinicians should recognise that such effects are infrequent and CHC may be prescribed with confidence.